Is abstinence really the best option? Exploring the role of exercise in the treatment and management of eating disorders. Issue 3 (4th May 2018) - Quesnel, Danika A.; Libben, Maya; D. Oelke, Nelly; I. Clark, Marianne; Willis-Stewart, Sally; Caperchione, Cristina M
ABSTRACT: Exercise prescription is suggested to help manage exercise abuse and improve overall eating disorder (ED) prognosis. This study explored emerging perceptions of ED health professionals concerning the role of exercise as a supportive treatment for EDs. Semi-structured interviews were conducted with international health professionals (n=13) with expertise in ED treatment. Verbatim transcripts were analyzed through thematic analysis. Four themes were revealed and titled 1) understanding the current state; 2) gaining perspectives; 3) barriers and benefits; 4) one size does not fit all. Within these themes, participants described the current state of exercise in ED treatment and suggested there exists a gap in research knowledge and practice. Participants also identified the implications of incorporating exercise into treatment and how an exercise protocol may be designed. Results enhance the understanding of the role of exercise in ED treatment and how it may further benefit individuals with EDs.